KRITIK FILSAFAT IBNU RUSYD SEBAGAI DASAR FILSAFAT ISLAM TERHADAP SIFAT-SIFAT KETUHANAN - SITI NURMALA; ENDAH ROBIATUL ADAWIYAH; BUNGA SEPTRIA VIONITA (JURNAL ILMIAH KOHESI, 2023)
Ibn Rushd himself in his philosophy admired Aristotle and even gave many reviews and comments on Aristotle's works. Ibn Rushd has many thoughts that form the basis of Islamic philosophy as well as various criticisms of several Islamic studies, including his philosophical criticism of the attributes of divinity, such as knowledge, life, etc. This study's research method is a qualitative research method with data collection techniques using literature (library research) which is to collect information or documents related to the concept of science according to Muslim figures such as biographies or other documents aimed at the object of research or collecting information from sources. literature. The purpose of this research is to gain knowledge about the philosophical criticism carried out by Ibn Rushd on the attributes of divinity with the criticism method carried out by Ibn Rushd and it is in criticizing theologians the demonstrative method that he employs. Because the demonstrative method is based on the use of reason, according to him The demonstrative method is considered as the most appropriate approach for obtaining answers to religious and philosophical.